Creating welcoming communities: Indonesian people with disabilities speak out - Widinarsih, Dini (Curtin University, 2018)
This is a qualitative participatory action research project conducted with a total of 43 Indonesian people with disabilities/PWDs, spanning one year. The original contributions of this study were the definition of disability awareness and disability awareness-raising, the disability awareness video guidelines, and the development of a disability awareness video based on those guidelines. These are the first definition, guidelines, and video that were created by Indonesian PWDs based on the social model of disability.